Forming the Institutional Environment for Innovation-based Development of Coal Enterprises - Drachuk, Yu.Z.; Trushkina, N.V. (Економічний вісник Донбасу, 2013)
The study analyzes basic indicators of innovationbased development of domestic enterprises in the field of fuel and energy resources production. The proposals have been worked out to form the institutional environment for the development of coal enterprises. У статті проаналізовано основні показники інноваційної діяльності вітчизняних підприємств у сфері видобування паливно-енергетичних копалин. Розроблено пропозиції щодо формування інституціонального середовища інноваційного розвитку вугільних підприємств. В статье проанализированы основные показатели инновационной деятельности отечественных предприятий в сфере добычи топливно-энергетических ископаемых. Разработаны предложения по формированию институциональной среды инновационного развития угольных предприятий.